2017
DOI: 10.1111/add.13720
|View full text |Cite|
|
Sign up to set email alerts
|

Purity, adulteration and price of drugs bought on‐line versus off‐line in the Netherlands

Abstract: In the article [1] published in the April 2017 issue of Addition, an error slipped into following sentence of the abstract: "There were no large differences in drug purity, yet small but statistically significant differences were found for 4-FA (on-line 59% versus off-line 52% purity for 4-FA on average, P = 0.001), MDMA powders (45 versus 61% purity for MDMA, P = 0.02), 2C-B tablets (21 versus 10 mg 2C-B/tablet dosage, P = 0.49) and ecstasy tablets (131 versus 121 mg MDMA/ tablet dosage, P = 0.05)." P = 0.49 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…34 These values are significantly higher than does reported for ATS street samples, where values ranged from 1.4 to 6% for traditional ATS samples. 35 Within these samples are also a wide range of impurities and street samples also containing from 3 to 10 cutting agents including caffeine, paracetamol, other illicit substances. This constantly changing composition of street samples, highlights a challenge for forensic analysis.…”
Section: Chemical Detectionmentioning
confidence: 99%
“…34 These values are significantly higher than does reported for ATS street samples, where values ranged from 1.4 to 6% for traditional ATS samples. 35 Within these samples are also a wide range of impurities and street samples also containing from 3 to 10 cutting agents including caffeine, paracetamol, other illicit substances. This constantly changing composition of street samples, highlights a challenge for forensic analysis.…”
Section: Chemical Detectionmentioning
confidence: 99%
“…Google-indexed webshops, social media, drug fora and cryptomarkets). Our own research showed that, in the Netherlands, only 15% of all online drug purchases could be identified as sourced through cryptomarkets [2]. In fact, the proportion of online sourced drugs is expected to be different from country to country, as exemplified by the huge differences between countries in the sourcing of drugs via cryptomarkets [3], seriously limiting the generalizability of debates about harms or benefits.…”
Section: Focus On Cryptomarkets and Online Reviews Too Narrow To Debamentioning
confidence: 99%
“…As the authors note, a reason for using cryptomarkets is that they are seen as offering quality products [2,3]. For drug sales, quality is an ambiguous and somewhat fuzzy concept, which can be misleading and even potentially harmful if misunderstood.…”
Section: Daan Van Der Gouwe Sander Rigter and Tibor Markus Bruntmentioning
confidence: 99%
“…
Commentary van der Gouwe et al (2017): Drug-testing services and cryptomarkets come of age Drug-checking services present an opportunity to improve public health awareness of illicitly manufactured drug supply chains and provide superior information on the purity and potency of drugs to people who use them. Important methodological questions remain regarding analytical protocols and dissemination of results.
…”
mentioning
confidence: 99%
“…This trend does not show signs of abating, despite concerted efforts by multi-lateral and national authorities to emergency schedule the resulting substances. Within this context, van de Gouwe et al [1] offer an elegant solution to protecting the health of people who use drugs, while simultaneously providing information for surveillance, both on-and off-line. Their paper is noteworthy, because it elegantly demonstrates the importance of drug testing services serving drug users, and highlights evolving differences between on-line and hand-to-hand markets.…”
mentioning
confidence: 99%